Perancangan Interior Sarana Kecantikan SEKAWAN Cosmetics Di Surabaya - Lisa Charisa (Intra, 2014)
Beautyis seenas one of thebasic needsof society at certain timesmust be met, namely the needtobe accepted. SEKAWAN Cosmeticsas ameans of presenting local cosmetic producers who workin the field of beauty services and sales. Facilities on offer are beauty shops, spas and salons, where the services provided by the products offered by SEKAWAN Cosmetics. The result ofthis designis expected tobe a placefor the public to appreciate beauty and to be fond of Indonesian cosmetics products.